2017
DOI: 10.1158/0008-5472.can-16-3062
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Lipid Synthesis Facilitates Gemcitabine Resistance through Endoplasmic Reticulum Stress in Pancreatic Cancer

Abstract: Pancreatic adenocarcinoma is moderately responsive to gemcitabine-based chemotherapy, the most widely used single agent therapy for pancreatic cancer. While the prognosis in pancreatic cancer remains grim in part due to poor response to therapy, previous attempts at identifying and targeting the resistance mechanisms have not been very successful. By leveraging TCGA dataset, we identified lipid metabolism as the metabolic pathway that most significantly correlated with poor gemcitabine response in pancreatic c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
146
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(150 citation statements)
references
References 55 publications
4
146
0
Order By: Relevance
“…Biosynthesis of heme and several phospholipid molecules were pathways uniquely associated with resistance to our nucleoside analogs. Both of these metabolic pathways have been described as important mechanisms of gemcitabine resistance and likely play a role in oxidative stress response (Miyake et al, 2010;Tadros et al, 2017). Overall, we saw that there was a weak positive correlation between enrichment across our screens and patient survival.…”
Section: Crispr Screening Reveals Drug Resistance Genesmentioning
confidence: 58%
“…Biosynthesis of heme and several phospholipid molecules were pathways uniquely associated with resistance to our nucleoside analogs. Both of these metabolic pathways have been described as important mechanisms of gemcitabine resistance and likely play a role in oxidative stress response (Miyake et al, 2010;Tadros et al, 2017). Overall, we saw that there was a weak positive correlation between enrichment across our screens and patient survival.…”
Section: Crispr Screening Reveals Drug Resistance Genesmentioning
confidence: 58%
“…Our lab demonstrated that by increasing glucose uptake and metabolic flux through the non-oxidative arm of pentose phosphate pathway, gemcitabine-resistant cancer cells increase pyrimidine synthesis which competes with gemcitabine incorporation [20]. Furthermore, we showed how pancreatic cancer relies on fatty acids biosynthesis for gemcitabine resistance [46]. A different approach to reduce gemcitabine resistance is through a glutamine analog.…”
Section: Discussionmentioning
confidence: 94%
“…The palmitate generated through de novo synthesis has a number of intracellular functions, including regulation of signaling networks in PDA and perturbations at multiple steps (ACC, FASN) attenuates PDA growth [83]. It has been recently reported that high FASN expression correlates with gemcitabine resistance in PDA and combination treatment of Orlistat (FASN inhibitor) and gemcitabine results in a synergistic response [84]. …”
Section: Introductionmentioning
confidence: 99%